Differentiation of metastatic lesions to the bones and multiple myeloma – a case study - Pachciński, Olaf; Przywara, Paulina; Raabe, Adam; Zaremba, Bartłomiej; Szudy-Szczyrek, Aneta; Hus, Marek (Journal of Education, Health and Sport, 2020)
Bones are one of the most common locations for cancer metastasis. Foci, which are in the most cases osteolytic, are located in the spine, ribs, pelvis, long bones. The etiology of changes varies widely as they can be observed in the course of breast, prostate or lung cancer and multiple myeloma. The aim of the study is to present the case of a 72-year-old female patient after right nephrectomy due to clear cell carcinoma with the presence of disseminated osteolytic foci in the bones located in the ribs, sternum and femur and the existance of calcified pulmonary nodules on diagnostic computed tomography (CT). Basing on the clinical data and imaging results, metastatic bone disease of kidney carcinoma was diagnosed. Despite the treatment, no clinical improvement was observed. In addition, general symptoms such as weakness, weight loss, bone pain appeared. Osteolysis and diffuse osteopenia with hypercalcaemia increased. Further diagnostics – a histopathological examination of the bone marrow combined with laboratory results allowed to make the correct diagnosis - multiple myeloma in stage III in Durie and Salmon classification, in stage 3 according ISS scale. The appropriate treatment was introduced. Patient received bortezomib-thalidomide-dexamethasone chemotherapy regimen and achieved very good partial response (VGPR). On the grounds of the case given, the key to successful treatment is to carry out detailed differentiation and to make an accurate diagnosis. Coexistence of another cancer should be always considered. A biopsy of pathological lesions is often the only way to diagnose disease.